Dream derby : the myth and legend of Black Gold - Hunter, Avalyn (Horses in history (University Press of Kentucky), 2023)
"On the morning of May 18, 1924, households across America opened their newspapers to the headline: "Derby Winner Property of Indian Woman." The woman in question was Rosa Magnet Hoots, a member of the Oklahoma Osage Nation. The horse, draped in the iconic red roses signifying his victory in the fiftieth running of the Kentucky Derby, was Black Gold. In a sport defined by its exclusivity, the pair's unlikely appearance in the winner's circle set off a firestorm of speculation that would uncover an origin story stranger than fiction. Named for the oil that had been discovered in large quantities in Oklahoma at the time of his birth, Black Gold was born in 1921 to a mare named Useeit. At the start of her hard-knocking racing career, Useeit had been purchased by Al Hoots, for whom she won thirty-two of a staggering 122 races. What the mare lacked in regality, she made up for in gumption, a trait Hoots believed could propel her progeny to the hallowed ground of Churchill Downs. Hoots himself would never see Black Gold, dying unexpectedly in 1917. But the legend that came to define the horse would begin with him. Languishing in his deathbed, Hoots claimed to have a prophetic dream that a colt born to Useeit would win the Kentucky Derby. He extracted a promise from his wife, Rosa, to breed the mare to the stallion Black Toney. The decision, which came to fruition three years after Hoots's death, would set in motion a story that would forever change Thoroughbred racing. In Dream Derby: The Myth and Legend of Black Gold, author Avalyn Hunter explores the personalities and histories that surrounded Black Gold. Told against the backdrop of a make-or-break moment for American horse racing and politics at large and framed by the racial violence that rocked Tulsa in the 1920s, Black Gold's victory at the Golden Jubilee stands at the intersection of sport and history. Hunter's work looks behind every stall and tack room door and celebrates the hard work that goes into a great horse and its rivals"--